Mid-term evaluation of the Improving Bean Productivity and Markets in Africa (IBPMA) project in Cameroon, Kenya, Tanzania, Rwanda, Uganda, and Zambia - PABRA (Pan-Africa Bean Research Alliance) (2023)
The Pan-Africa Bean Research Alliance (PABRA) through the Improving Bean Productivity and Markets in Africa (IBPMA) Project funded by the Global Affairs Canada engaged on the project to reduce poverty amongst smallholder bean farmers, especially women, by reducing food insecurity, increasing incomes, and strengthening climate-smart agriculture (CSA). This mid-term evaluation report has brought up some key findings about the progress the project made over the four-year implementation period. Results show that PABRA through partners has promoted pluralistic seed supply systems that combined public and private sector actors. Public and private sector actors have complementary roles that bolstered the project success. Interdependence between actors is key for the successful development of the corridor. However, private-sector firms in seed distribution need to invest in branding and marketing their products to gain recognition among farmers and differentiate from the roles played by national partners. The emerging private sector-led bean seed system needs nurturing and further support towards maturity. Measures are needed to promote seed supply chain integrity and compliance with seed regulations in the different countries.